Soluble Endothelial Cell-Selective Adhesion Molecule and Incident Cardiovascular Events in a Multi-Ethnic Population - Ren, Hao-Yu (Am Heart J, 2017)
BACKGROUND: Cell adhesion molecules are key regulators of atherosclerotic plaque development, but circulating levels of soluble fragments, such as intercellular adhesion molecule (sICAM-1) and vascular cell adhesion molecule (sVCAM-1), have yielded conflicting associations with atherosclerotic cardiovascular disease (ASCVD). Endothelial cell-selective adhesion molecule (ESAM) is expressed exclusively in platelets and endothelial cells, and soluble ESAM (sESAM) levels have been associated with prevalent subclinical atherosclerosis. We therefore hypothesized that sESAM would be associated with incident ASCVD. METHODS: sESAM, sICAM-1, and sVCAM-1 were measured in 2,442 participants without CVD in the Dallas Heart Study, a probability-based population sample age 30–65 enrolled between 2000–2002. ASCVD was defined as first myocardial infarction, stroke, coronary revascularization, or CV death. A total of 162 ASCVD events were analyzed over 10.4 years. RESULTS: Increasing sESAM was associated with ASCVD, independent of risk factors (HR Q4 vs. Q1: 2.7, 95% CI 1.6–4.6). Serial adjustment for renal function, sICAM-1, VCAM-1, and prevalent coronary calcium did not attenuate these associations. Continuous ESAM demonstrated similar findings (HR 1.31 95% CI 1.2–1.4). Addition of sESAM to traditional risk factors improved discrimination and reclassification (delta c-index: p=0.009; IDI p=0.001; NRI = 0.42, 95% CI 0.15–0.68). Neither sICAM-1 nor sVCAM-1 was independently associated with ASCVD. CONCLUSIONS: sESAM but not sICAM-1 or sVCAM-1 levels are associated with incident ASCVD. Further studies are warranted to investigate the role of sESAM in ASCVD.